Sustained W-melting experiments on actively cooled ITER-like plasma facing unit in WEST. (8th November 2021) - Corre, Y; Grosjean, A; Gunn, J P; Krieger, K; Ratynskaia, S; Skalli-Fettachi, O; Bourdelle, C; Brezinsek, S; Bruno, V; Chanet, N; Coenen, J; Courtois, X; et al.
Abstract: The consequences of tungsten (W) melting on divertor lifetime and plasma operation are high priority issues for ITER. Sustained and controlled W-melting experiment has been achieved for the first time in WEST on a poloidal sharp leading edge of an actively cooled ITER-like plasma facing unit (PFU). A series of dedicated high power steady state plasma discharges were performed to reach the melting point of tungsten. The leading edge was exposed to a parallel heat flux of about 100 MW.m −2 for up to 5 s providing a melt phase of about 2 s without noticeable impact of melting on plasma operation (radiated power and tungsten impurity content remained stable at constant input power) and no melt ejection were observed. The surface temperature of the MB was monitored by a high spatial resolution (0.1 mm/pixel) infrared camera viewing the melt zone from the top of the machine. The melting discharge was repeated three times resulting in about 6 s accumulated melting duration leading to material displacement from three similar pools. Cumulated on the overall sustained melting periods, this leads to excavation depth of about 230 μ m followed by a re-solidified tungsten bump of 200 μ m in the JxB direction.